Mapping the contents of forest fire in the Conifer Forest natural protected area of Flora and Fauna: Maderas del Carmen, Coahuila - Brondi Rueda, Néstor Fabián (2016)
Fire is an important element in the development of ecosystems, however when it is spread out of control in areas such as forests and woodlands, the negative effects to the environment and ecosystems are considerable. The Natural Protected Area of Flora and Fauna of Maderas del Carmen (ANPFFMC) is no exception, so the main objective of this work was mapping the rate of forest fuel from the forest of conifers of the ANPFFMC, through the estimation of dead fuels and the burden of the organic layer. 22 conglomerates were sampled, the vegetation was delimited through the classification of a Landsat-8 satellite image. The results allowed mapping the rate of risk of forest fire through the statistical interpolation method “spline with barriers” generating a barrier of the supervised image interpolation. The average values obtained for 1 hour fuels were 1.22 t-ha-1, to 5.24 hours t-ha-1, for 1,000 hours ((With rot) 27.56 t ha-1. The average weight of the load of the organic layer was 27.56 t-ha-1 with an average depth of 2.35 cm.